A hierarchical LDH/MOF nanocomposite: single, simultaneous and consecutive adsorption of a reactive dye and Cr(vi). Issue 16 (5th April 2020) - Soltani, Roozbeh; Marjani, Azam; Shirazian, Saeed
Abstract : A hierarchical trimodal micro-meso-macroporous LDH/MOF nanocomposite as a superior adsorbent for single, simultaneous and consecutive adsorption of a reactive dye and Cr(vi ). Abstract : The design and development of an environmentally benign porous adsorbent for effective simultaneous adsorption of organic dyes and heavy metals from water are important but remain a big challenge. Herein, we have designed a layered double hydroxide/metal–organic framework-based hierarchical nanocomposite (LDH/MOF HNC) by a facile, room-temperature in situ approach. This paper for the first time reports a hierarchical trimodal micro-meso-macroporous LDH/MOF composite with a high surface area (surface area 1282 m 2 g −1 and pore volume 0.93 cm 3 g −1 ), synthesised by uniformly growing MOF nanocrystals on the surface of LDH nanosheet ultrathin films. An attempt is made to quantitatively demonstrate the adsorption data via suitable nonlinear kinetic and isotherm equations for single, simultaneous, and consecutive adsorption of the orange II reactive dye and Cr(vi ). Experiments were performed at various values of pH (6.0–11.0), adsorbent dosages (1.0–8.0 mg), adsorbate concentrations (5–500 mg L −1 ), and temperatures (293–323 K). The Langmuir model revealed a satisfactory fit to the equilibrium data of the LDH/MOF HNC (correlation coefficients R 2 > 0.98) with a calculated maximum adsorption capacity of 1173 and 733 mg g −1 for orange II and Cr(vi ), respectively, in a simultaneous adsorption system. The results of the study demonstrated that LDH/MOF HNCs could potentially be applied as a promising nanoadsorbent for the simultaneous removal and extraction of toxic dyes and metals from water.